Little Albert still missing - Powell, Russell A. (My University, 2010)
Comments on the article by H. P. Beck, S. Levinson, & G. Irons. Beck, Levinson, and Irons presented a fascinating account of how they seemingly solved the mystery of whatever happened to Little Albert, the infant in whom Watson and Rayner (1920) claimed to have conditioned a rat phobia.
Keywords: John Broadus Watson; Little Albert; child psychology; conditioned emotional response; history of psychology